Gender-differentiated effects of parenthood on earnings: understanding cross-national variation in the motherhood penalty and fatherhood bonus - Fernandez Salgado, Marina (Luxembourg, 2012)
"Although mothers are increasingly joining the labor force, employers continue to pay mothers less than non-mothers and fathers more than non-fathers. Using data from the Luxembourg Income Study (LIS), this paper investigates the influence of parental status on the incomes of men and women in eight industrialized countries. I demonstrate the existence of an employer bias against mothers in all countries except the Netherlands and a bias toward fathers in all countries except the Netherlands and Luxembourg. I then compare three methods for categorizing countries based on gender equality to see which best explains the cross-national variation in motherhood penalties and fatherhood bonuses."